PELATIHAN PERENCANAAN BISNIS BAGI BUMDES DI BAUMATA - Selfiana Goetha; Alfry Aristo J. Sinlae; Paskalis A. Nani; Maria Augustin Lopes Amaral; Adrianus Ketmoen (Universitas Majalengka, 2023)
The villages of Baumata and Baumata Timur have the potential to develop businesses such as coconut, banana, and clean water. Still, the BUMDes management needs to make an optimal business plan so this community service occurs. The Widya Mandira Catholic University team aims to provide knowledge and skills to grow your business further. The implementation method is business planning training. A business plan is used to efficiently and effectively operate a business that will be or is being run, ensures maximum profits, and seek third-party funding. Keywords: village economy, business plan, BUMDes